Lyme borreliosis: insights into tick-/host-borrelia relations - Grubhoffer, Libor; Golovchenko, Maryna; Vancová, Marie; Zacharovová-Slavícková, Klara; Rudenko, Nataliia; Oliver, James H (Folia parasitologica, 2005)
Lyme borreliosis (LB) is a serious infectious disease of humans and some domestic animals in temperate regions of the Northern Hemisphere. It is caused by certain spirochetes in the Borrelia burgdorferi sensu lato (s.l.) species complex. The complex consists of 11 species (genospecies). Borrelia burgdorferi sensu stricto (s.s.), Borrelia garinii and Borrelia afzelii are the major agents of human disease. Borrelia burgdorferi s.l. species are transmitted mainly by ticks belonging to the Ixodes ricinus species complex plus a few additional species not currently assigned to the complex. B. burgdorferi infections may produce an acute or chronic disease with a wide array of clinical symptoms such as erythema migrans (EM), carditis, arthritis, neuroborreliosis, and acrodermatitis chronica atrophicans (ACA). Differences in LB spirochetes 'genospecies' and strains/isolates determine the occurrence and severity of this multi-system disease. Accurate and reliable identification of the LB spirochetes in ticks as well as knowledge of their prevalence are essential for prevention against the disease and development of an effective vaccine. An overview of the knowledge of molecular factors with emphasis on potential protein-carbohydrate interactions in the tick-borrelia system is the main focus of this review.
Keywords: Ixodes; Antigens, Bacterial; Humans; glykokonjugáty; Hemocytes; Borrelia burgdorferi Group; Arachnid Vectors; Lyme Disease; lymeská nemoc; hemocyty; Host-Parasite Interactions; klíště; antigeny bakteriální; lektiny; lidé; zvířata; arachnida jako vektory; Lectins; Borrelia burgdorferi komplex; Glycoconjugates; Animals; interakce hostitele a parazita